The Effect of Prescription Isodose Variation on Tumor Control and Toxicities in Stereotactic Radiosurgery for Sporadic Vestibular Schwannoma: Propensity Score-Matched Case–Control Study - Teyateeti, Achiraya; Graffeo, Christopher S.; Perry, Avital; Tryggestad, Eric J.; Brown, Paul D.; Pollock, Bruce E.; Link, Michael J. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objective Vestibular schwannoma (VS) treated with Gamma Knife stereotactic radiosurgery (SRS) was typically performed at 50% isodose line (IDL50); however, the impact of IDL variation on outcomes is poorly understood. This study aimed to compare tumor control (TC) and toxicities between treatment at 40% (IDL40) and 50% (IDL50).Methods Sporadic/unilateral VS patients treated with SRS dose 12 to 14 Gy and prescription isodose volume ≤10cm3 were included. Propensity score matching was applied to IDL40 cohort to generate an IDL50 companion cohort, adjusting for age and prescription isodose volume. After exclusion of patients with follow-up <24 months, there were 30 and 28 patients in IDL40 and IDL50 cohorts, respectively.Results Median follow-up time was 96 months (24–225 months). Actuarial and radiographic TC rates were 91.8% and clinical TC was 96.2% both at 5 and 10 years. TC was higher in IDL40 cohort but not significant (96.4 vs. 86.7%; p = 0.243). Hearing preservation (HP) rates were 71.9 and 39.2% at 5- and 10-year intervals, with significantly higher rates of HP noted in IDL40 cohort (83.3 vs. 57.1% at 5-year interval; 62.5 vs. 11.4% at 10-year interval; p = 0.017). Permanent facial neuropathy occurred in two patients, both from the IDL50 cohort (3.5%). Rates of post-SRS steroid treatment or shunt placement for hydrocephalus were slightly higher in IDL50 patients (6.9 vs. 17.9%; p = 0.208 and 3.3 vs. 7.1%; p = 0.532).Conclusion For treatment of VS with SRS, dose prescription at IDL40 or IDL50 provides excellent long-term TC and toxicity profiles. IDL40 may be associated with improved long-term HP.
Keywords: vestibular schwannoma; acoustic neuroma; radiosurgery; Gamma Knife; isodose line; hearing preservation; facial neuropathy; propensity score matched